Synthesis of functionalized derivatives of the gamma-secretase modulator BMS-932481 and identification of its major metabolite. Issue 22 (15th November 2020) - Zhang, Yunhui; Boy, Kenneth M.; Wu, Yong-Jin; Ramirez, Antonio; Toyn, Jeremy H.; Ahlijanian, Michael K.; Albright, Charles F.; Zhuo, Xiaoliang; Johnson, Benjamin M.; Denton, R. Rex; Olson, Richard E.; Thompson, Lorin A.; et al.
Graphical abstract: Abstract: In an effort to improve physical properties by introducing polar functionality into the bicyclic pyrimidine gamma-secretase modulator (GSM) clinical candidate BMS-932481, we prepared several oxidative products of BMS-932481. Among the analogs that were prepared, the C-5 alcohol 3 was identified as the predominant metabolite of BMS-932481 found in rat and human liver microsomes. Alcohol 3 was determined to be chemically unstable, leading to the hypothesis that 3 may lead to the production of reactive species both in vitro and in vivo .